Sound Communication in Embryos and Hatchlings of Lepidochelys kempii - Ferrara, Camila Rudge; Vogt, Richard Carl; Sousa-Lima, Renata S.; Lenz, Anna; Morales-Mávil, Jorge Eufrates (Chelonian Conservation and Biology, 2019)
Recent studies have shown that acoustic signals play an important role in turtle social behavior and reproduction. We recorded embryos and hatchlings of Lepidochelys kempii inside the nest and underwater in June 2016 in Playa Santander, Veracruz, Mexico, and detected 189 sounds that were classified into 6 types according to their aural and spectral characteristics. Our results show that acoustic communication appears to be widely used in all species of sea turtles in aquatic environments, probably because of the high efficiency of this signaling modality in water compared with air. © 2019 Chelonian Research Foundation.